Development of thermo-responsive ionic liquid as draw solution and its performance in forward osmosis - Mohd Amirul Mukmin, Abdullah (2020)
Desalination based on membrane technology is one of the approaches which has been extensively explored to tackle the challenge in increasing demand of clean water. Although reverse osmosis (RO) process has been applied for a long time, the promising forward osmosis (FO) membrane desalination is viewed as a potentially viable energy efficient performance technology. But, the main problem in FO process is the lack of suitable draw solutes that can be efficiently regenerated. A distinct advantage using thermo-responsive ionic liquids (TRILs) is the efficient in regenerating the draw solute via thermally stimulation. In this study, 10 cations and two anions were selected from COSMO-RS database and van’t Hoff factor prediction. 11 type of ILs was successfully synthesized via metathesis and neutralization method. The synthesized ILs were mixed with water and were cooled to 0 °C and then gradually heated to 70 °C to screen critical temperature. When a solution was found to be phase-separated above its critical temperature, this mixture underwent the lower critical solution temperature (LCST) type phase transition and which contrary with upper critical solution temperature (UCST) behavioral. The interactions mechanism of TRILs with water were examined using COSMO-RS simulation and H NMR for selected ILs. The TRILs were tested in FO process as draw solution and achieved high water flux 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim][BF4]) (0.71 LMH) and tetrabutylphosphonium trifluoroacetate ([P4444][TFA]) (0.44 LMH) compared to NaCl (0.33 LMH). The [Bmim][BF4] was selected as draw solution and aquaporin membrane with pressure retarded osmosis (PRO) mode was used to evaluate the effect of parameter and optimal condition for FO process. The 2-Level factorial experiment design was used to study the effect of parameters such as feed and draw flowrate, draw solution concentration, temperature and type of flow with feed concentration using artificial seawater (0.6 M NaCl). The draw solution concentration and the interactions between draw and feed flowrate was the most significant factors to achieve high water flux 5.1 LMH. Besides that, the draw flowrate and the interaction of draw flowrate and feed flowrate give high significant negative effect which is good to obtain low reverse salt 1.3 gMH. The desirability function (DF) was used, in order to obtain the highest water flux 5.04 LMH and the lowest reverse salt flux 1.71 gMH with 0.95 desirability. The optimal condition for FO performance is 300 ml/min feed and draw flowrate with 3.0 M draw solution at 25 °C and co-current flow. In this research, the phase separation via thermally stimulated liquid -liquid phase separation was achievable. The traceable amount of [Bmim][BF4] in water rich phase was detected using UV-Vis spectroscopy and purified using nanofiltration (NF). The water spinach was selected to study the effect of traceable amount of ILs in water on plant growth and acceptable traceable amount of [Bmim][BF4] is below 500 ppm. Based on the findings, it can be concluded that, [Bmim][BF4] is alternatively suitable to be use as draw solution in FO process.